2000
DOI: 10.4081/jbr.2000.10721
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intracellular Calcium Ions in the Physiopathology of Fibromyalgia Syndrome

Abstract: Today fibromyalgia syndrome (FM) is considered to be a generalized nonarticular rheumatic condition. It shows typical symptoms such as chronic pain, asthenia, muscular tension and/or rigidity in articular, periarticular subcutaneous tissues, ligaments and tendon insertions. It is associated with a specific tenderness on palpation at tender points (TP)(l,2). FM is one of the most frequent rheumatic diseases affecting from 6% to 20% of rheumatology out-patients. It has a higher incidence in women aged between 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…43,44 Bir çalışmada, FMS'li hastaların serum magnezyum düzeylerinin normal olduğu ancak lökosit içi magnezyum düzeylerinin ise azaldığı sunulmuştur. 45 Diğer bir çalışmada ise serum magnezyum seviyeleri ile kas performansı ve çeşitli kas parametreleri arasında güçlü ve bağımsız bir ilişki olduğu gösterilmiştir. 46 Çalışmamızda FMS hastalarının kan magnezyum seviyelerinin denge ve düşme riski durumlarını etkilemediği tespit edildi.…”
Section: Discussionunclassified
“…43,44 Bir çalışmada, FMS'li hastaların serum magnezyum düzeylerinin normal olduğu ancak lökosit içi magnezyum düzeylerinin ise azaldığı sunulmuştur. 45 Diğer bir çalışmada ise serum magnezyum seviyeleri ile kas performansı ve çeşitli kas parametreleri arasında güçlü ve bağımsız bir ilişki olduğu gösterilmiştir. 46 Çalışmamızda FMS hastalarının kan magnezyum seviyelerinin denge ve düşme riski durumlarını etkilemediği tespit edildi.…”
Section: Discussionunclassified
“…Although disturbances in the musculoskeletal system, the neuro-endocrine system and in the central nervous system have been implicated in the pathophysiology of FM, a primary mechanism underlying the etiopathogenesis of FM is unknown (17) . Serum trace element levels have been researched to reveal etiopathogenesis of patients with FM (18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%
“…Metals like calcium and magnesium compete with each other in modulating muscle contraction as well as in regulating many enzymatic reactions involved in energy metabolism, signal transduction and brain activity. Results concerning levels of calcium and magnesium in Fm are to some extent controversial; some authors observed reduced serum calcium and calcitonin levels in a small sample of FM patients (16) , while others report a normal range of plasma calcium and magnesium levels in patients affected by FM together with their reduced concentrations inside polymorphonuclear leukocytes (17) .Inorganic phosphorus is critical for numerous normal physiologic functions including skeletal development, mineral metabolism, cell membrane phospholipid content and function, cell signaling, platelet aggregation, and energy transfer through mitochondrial metabolism (18) .…”
Section: Introductionmentioning
confidence: 99%